2010
DOI: 10.1038/bmt.2010.314
|View full text |Cite
|
Sign up to set email alerts
|

BU- vs TBI-based conditioning for adult patients with ALL

Abstract: Evidence suggests an advantage for TBI over BU as a component of conditioning regimens for allogeneic hematopoietic cell transplant in patients with ALL. We have employed both TBI and BU for conditioning in ALL and reviewed our experience to compare outcomes. From July 1989 to June 2008, we identified 86-adult ALL patients treated with either a TBI-or BU-based regimen and transplanted with either a well-matched sibling or unrelated donor. Data including demographics, immunophenotype, disease status and cytogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 11 publications
1
13
1
Order By: Relevance
“…[46][47][48][49][50] Although TBI-based regimens are widely used in HSCT, excellent outcomes of BU-based regimens were also reported by several single institution trials. We observed a superiority of BU/CY-based regimen over TBI/CY-based regimen on 1-year PFS in this co-infusion approach.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48][49][50] Although TBI-based regimens are widely used in HSCT, excellent outcomes of BU-based regimens were also reported by several single institution trials. We observed a superiority of BU/CY-based regimen over TBI/CY-based regimen on 1-year PFS in this co-infusion approach.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in our sibling donor cohort, the use of TBI did not result in superior outcomes as compared with non-TBI regimen (see Results). Although some studies demonstrated superior outcome using TBI as compared with BUCY after matched donor HSCT (31,32), other reports did not find significant difference between TBI or non-TBI regimen for patients transplanted in CR (33,34). Due to inconvenient TBI facilities and worry about the fertility, the uniform protocol (non-TBI) with our T-cell-replete modality was implemented in our haploidentical study population.…”
Section: Discussionmentioning
confidence: 99%
“…BU is a potent inducer of apoptosis in ALL cells 6 and has been evaluated in myeloablative doses with CY in order to avoid TBIrelated toxicity in ALL patients. [7][8][9] In pediatric patients, BU was inferior to TBI; however, pharmacokinetic dose adjustment was not done and, because of a higher clearance of BU in children, subtherapeutic BU exposures may have accounted for the outcome. In addition, poor results with BU may be explained by erratic oral absorption that results in as much as a 10-fold range of systemic exposures, with excess toxicity at high exposure and lack of efficacy at low exposure.…”
Section: Introductionmentioning
confidence: 99%